Peranan Sulfur Bagi Pertumbuhan Tanaman - Nana Danapriatna (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2008)
Sulfitr is a secondary plant nutrients to make the amino acids cystine, cysteine and methionine and is part of biotin, thiamine, co-enzyme A and glutationin in plants. Suljur also Junctions as an activator, cofactor or regulator of enzymes and plays a role in plant physiological processes and the formation of chlorophyll. Plants take the sulfitr in the form of SO4 2 anion derived from organic matter, soil minerals and fertilizer. The use of high analysis fertilizer resulted in the emergence of sulfur deficiency symptoms in various agricultural areas. Therefore, the provision of fertilizer sulfitr or sulfitr fertilizer carrier needs to be done to correct it.